Model Pemberdayaan Kelompok Ternak Kelinci melalui Program Pelatihan Pertanian dan Perdesaan Swadaya (studi kasus Kelompok Ternak Kelinci “Mandiri Jaya” di Desa Ngijo, Kecamatan Karangploso, Kabupaten Malang) (Faculty of Animal Science, Universitas Brawijaya, 2017)
The purpose of this research was to learn the model of empowerment to a rabbit farmer group which is named “Mandiri Jaya” through Agriculture Training and Self Supporting of Rural Program. This research employs survey method. This qualitative research choosed its key informants by using purposive sampling that was followed by Snowball sampling. The result of this research is the model of empowerment that was given to the rabbit farmer group which includes training provided of rabbits, human development, community development, and business development. Various forms of the training are given once in month for annualy. The material training provided includes how to manage the rabbit farmer group, so becomes profitable. For examples how to choose proper and high-quality feed, and to build a good housing system for the rabbit. The material of human development is given so the rabbit farmer group can develop the ideas, exchange their ideas and information with other members. The material of community development is given so that the farmers that are involved know how to build a safe and clean environment especially near the rabbit housing area. The material of business development is given so that the member of the group know how to be a good entrepreneur and the group becomes more advanced.